Materials and preparation methods for glass slides at the tip of micro-electronic endoscopes

By combining the modified polyimide microspheres with resin, the problem of insufficient anti-static discharge breakdown performance of the medical electronic endoscope precipitation module after the finer diameter is solved, and the high transparency and high breakdown resistance is achieved, which is suitable for the preparation of precipitation slides of microelectronic endoscopes.

CN119751925APending Publication Date: 2025-04-04MAXENMED GUANGZHOU
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411991318.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

After the thinning of the existing medical electronic endoscope precursor modules, it is difficult to take into account both optical transparency and anti-static discharge breakdown performance, resulting in poor electrostatic protection.

Method used

Modified polyimide microspheres are used to react with acrylate monomers by grafting silane coupling agent to form core-shell microspheres, and combined with PC resin and PMMA resin to prepare alloy materials to improve breakdown resistance.

Benefits of technology

While ensuring optical transparency, it significantly improves the breakdown resistance of the microelectronic endoscope precipitation slide, which can effectively protect the internal ESD-sensitive devices, and is suitable for ultra-fine diameter microelectronic endoscopes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223712140000031
    Figure BDA0005223712140000031
  • Figure BDA0005223712140000071
    Figure BDA0005223712140000071
  • Figure BDA0005223712140000072
    Figure BDA0005223712140000072
Patent Text Reader

Abstract

The present invention discloses a material for a tip glass slide of a micro-electronic endoscope and a preparation method thereof. The material is prepared from PC resin, PMMA resin, modified polyimide microspheres, compatibility, and antioxidants. The modified polyimide microspheres are obtained by reacting polyimide microspheres grafted with silane coupling agents with acrylate monomers, and the polyimide microspheres grafted with silane coupling agents are obtained by reacting polyamic acid solution with silane coupling agents. When the material of the present invention is made into a tip glass slide of a micro-electronic endoscope, it greatly improves the anti-puncture performance while ensuring the imaging effect of the endoscope, and therefore can provide protection for the tip module of an ultra-fine-caliber micro-electronic endoscope.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medical devices, and more specifically, the present invention relates to a modified polyimide microsphere, an alloy material and an application thereof in preparing a tip glass slide of a micro electronic endoscope. Background Art

[0002] Based on the needs of minimally invasive clinical surgery and medical diagnosis of human microcavities, ultra-fine diameter is the main development direction of medical electronic endoscopes. However, after the medical electronic endoscope is thinned, there is a technical problem that it is difficult to improve the anti-electrostatic discharge resistance of the front module. One of the main reasons for the problem is that the existing materials cannot take into account both optical transparency and anti-electrostatic discharge breakdown performance when used to prepare the front glass slide.

[0003] The electrostatic protection of the endoscope tip module is provided by the internal anti-static circuit and the external tip module protection device. The tip module protection device is usually composed of a tip glass and a tip housing ( Figure 1 ), where the tip glass is the optical window of the electronic endoscope. In addition to providing insulation isolation, this part of the material also needs to have high transparency to provide a clear field of view for the image acquisition module.

[0004] When the tip of the endoscope is reduced in diameter, in order to leave space for the internal module to be assembled, it is usually necessary to minimize the size and wall thickness of the tip glass. The commonly used materials used to make the tip glass, such as polyethylene terephthalate (PET), cyclic olefin copolymer (COC), polycarbonate (PC), etc., are easily broken down by electrostatic discharge when made into thin-walled small-diameter protective devices, and cannot provide ideal insulation performance.

[0005] In current technology, functional modified fillers are often used to improve the anti-static breakdown performance of the tip glass of ultra-fine-caliber endoscopes. However, this method cannot avoid the decrease in optical transparency caused by filler stacking or agglomeration. In order to improve the dispersion of the filler to increase optical transparency, the anti-static breakdown performance is usually sacrificed, and it is difficult to balance the two. Summary of the invention

[0006] Based on this, the object of the present invention is to provide a material for preparing a tip glass slide of a micro electronic endoscope that has both optical transparency and high dielectric strength, which can improve the breakdown voltage of the tip glass slide at a small size and low thickness without sacrificing optical transparency.

[0007] The specific technical solutions for achieving the above-mentioned invention objectives include the following.

[0008] The first aspect of the present invention provides a modified polyimide microsphere, which is obtained by reacting polyimide microspheres grafted with a silane coupling agent and an acrylate monomer in a mass ratio of 1:1 to 2, wherein the polyimide microspheres grafted with a silane coupling agent are obtained by reacting a polyamic acid solution with a silane coupling agent; the concentration of the polyamic acid solution is 0.5wt% to 1.5wt%, and the amount of the silane coupling agent added is 0.5% to 1% of the volume of the polyamic acid solution.

[0009] The second aspect of the present invention provides a method for preparing the modified polyimide microspheres, comprising the following steps:

[0010] (1) adding the silane coupling agent to the polyamic acid solution, reacting at 170° C. to 190° C. for 0.8 h to 1.2 h, then dropping an excess amount of a mixed solution of pyridine and acetic anhydride in a molar ratio of 0.8 to 1.2:1, reacting at 170° C. to 190° C. for 3 h to 5 h; then heating at 280° C. to 320° C. for 0.8 h to 1.2 h, and cooling to obtain polyimide microspheres grafted with the silane coupling agent;

[0011] (2) Under the protection of inert gas, the polyimide microspheres grafted with silane coupling agent, ultrapure water dispersed with surfactant, and methanol are heated to 60° C. to 80° C., and then the catalyst and the acrylate monomer are added in sequence, reacted at 60° C. to 80° C. for 18 h to 22 h, and demulsified to obtain modified polyimide microspheres.

[0012] The third aspect of the present invention provides an alloy material, which is prepared from the following raw materials in parts by weight:

[0013]

[0014] The fourth aspect of the present invention provides a method for preparing the above-mentioned alloy material, comprising the following steps: uniformly stirring PMMA resin and modified polyimide microspheres, then adding PC resin, compatibilizer, and antioxidant to continue mixing and stirring, and sequentially melting, extruding, and granulating in a twin-screw extruder to obtain the alloy material.

[0015] According to a fifth aspect of the present invention, there is provided a micro electronic endoscope tip glass slide, which is obtained by injection molding the above alloy material into a cylindrical rod and then cutting it into slices.

[0016] The present invention first provides a modified polyimide microsphere obtained by twice modification, which has a core-shell structure, a shell thickness of 10nm-40nm, and a particle size of 100nm-350nm, and uses the modified polyimide microsphere as a filler to prepare an alloy material with PC resin, PMMA resin and other components, and at the same time, by adjusting the distribution ratio of each component within a suitable range, the tip glass slide of a micro-electronic endoscope made of the alloy material can greatly improve the anti-puncture performance while ensuring the imaging effect of the endoscope, thereby providing protection for the tip module of an ultra-fine caliber micro-electronic endoscope.

[0017] The inventors found that the modified polyimide microspheres prepared by the present invention can be used in PC / PMMA alloy materials. On the one hand, charge trap sites can be introduced at the resin matrix-microsphere interface, which can hinder the movement of high-energy electrons and the propagation of breakdown paths, increase the breakdown voltage of the alloy material itself, and make the alloy material less than 1mm in size and less than 250μm in wall thickness. Thin-walled tip glass slides can also achieve compliant electrostatic breakdown protection for internal ESD sensitive devices; on the other hand, because the modified polyimide microspheres are coated with PMMA on the shell layer, they can achieve good dispersion effects in polycarbonate and polymethyl methacrylate matrix resins, forming a uniform material. When preparing the tip glass slide of a micro-electronic endoscope, the imaging effect of the endoscope can be minimized, ensuring clear vision and obtaining high-quality imaging. Moreover, due to the uniform dispersion of the modified polyimide microspheres described in the present invention, the problems of particle stacking agglomeration and interface defects can be effectively reduced, and the possibility of static electricity breakdown at the resin matrix can be reduced. Compared with the alloy material prepared using unmodified polyimide microspheres, it has significantly better electrostatic breakdown protection effect and transparency. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the structure of the tip of a microelectronic endoscope; 1. Endoscope tip module protection device; 2. Tip glass slide; 3. Tip housing.

[0019] Figure 2 Graph showing the particle size of the modified polyimide microspheres prepared in Example 1 of the present invention.

[0020] Figure 3 Schematic diagram of the shell thickness of the modified polyimide microspheres prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0022] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0023] Unless otherwise specified, the examples are all based on conventional experimental conditions or the conditions recommended by the manufacturer's instructions. The sources of the raw materials described in the present invention are not particularly limited, and commercially available products known to those skilled in the art can be used. The raw materials used in the following examples of the present invention are all commercially available products.

[0024] In some embodiments of the present invention, a modified polyimide microsphere is disclosed, which is obtained by reacting a polyimide microsphere grafted with a silane coupling agent with an acrylate monomer, wherein the polyimide microsphere grafted with a silane coupling agent is obtained by reacting a polyamic acid solution with a silane coupling agent. The modified polyimide microsphere obtained by the present invention has a core-shell structure, wherein the inner layer, the silane coupling agent, and the acrylate are respectively PI, the silane coupling agent, and the acrylate.

[0025] In some of the embodiments, the mass ratio of the polyimide microspheres of the grafted silane coupling agent to the acrylate monomer is 1:1-2.

[0026] In some of the embodiments, the mass ratio of the polyimide microspheres of the grafted silane coupling agent to the acrylate monomer is 1:1.5-1.7.

[0027] In some of the embodiments, the mass ratio of the polyimide microspheres of the grafted silane coupling agent to the acrylate monomer is 1:1.6-1.7.

[0028] In some embodiments, the concentration of the polyamic acid solution is 0.5 wt% to 1.5 wt%, and the amount of the silane coupling agent added is 0.5% to 1% of the volume of the polyamic acid solution.

[0029] In some embodiments, the concentration of the polyamic acid solution is 0.8 wt % to 1.2 wt %, and the amount of the silane coupling agent added is 0.7 wt % to 0.8 wt % of the volume of the polyamic acid solution.

[0030] In some embodiments, the concentration of the polyamic acid solution is 0.9 wt % to 1.1 wt %, and the amount of the silane coupling agent added is 0.74 wt % to 0.76 wt % of the volume of the polyamic acid solution.

[0031] In some embodiments, the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, and γ-aminopropylmethyldimethoxysilane.

[0032] In some embodiments, the silane coupling agent is γ-aminopropyltriethoxysilane (KH550).

[0033] In some embodiments, the acrylate monomer is one or more of benzyl methacrylate, phenyl methacrylate, and naphthyl methacrylate.

[0034] In some embodiments, the acrylate monomer is phenyl methacrylate.

[0035] In other embodiments of the present invention, a method for preparing the modified polyimide microspheres is disclosed, comprising the following steps:

[0036] (1) adding a silane coupling agent to a polyamic acid solution, reacting at 170° C. to 190° C. for 0.8 h to 1.2 h to obtain a polyamic acid solution grafted with a silane coupling agent; dropping an excess amount of a mixed solution of pyridine and acetic anhydride in a molar ratio of 1:1, reacting at 170° C. to 190° C. for 3 h to 5 h; then heating at 280° C. to 320° C. for 0.8 h to 1.2 h, and cooling to obtain polyimide microspheres grafted with a silane coupling agent;

[0037] (2) Under the protection of inert gas, polyimide microspheres grafted with silane coupling agent, ultrapure water dispersed with surfactant, and methanol are heated to 60°C to 80°C, and then catalyst and acrylate monomer are added in sequence. The mixture is reacted at 60°C to 80°C for 18h to 22h, and the emulsion is broken to obtain modified polyimide microspheres.

[0038] In some of the embodiments, the catalyst is one or more of chloroauric acid tetrahydrate, chloroplatinic acid hexahydrate, ferrous chloride tetrahydrate, cyclopentadiene platinum chloride, and cyclooctadiene platinum chloride.

[0039] In some embodiments, the catalyst is cyclopentadienylplatinum chloride.

[0040] In some of the embodiments, the amount of the catalyst is 0.03% to 0.1% by weight of the acrylate monomer.

[0041] In some of the embodiments, the amount of the catalyst used is 0.05% to 0.1% by weight of the acrylate monomer.

[0042] In some of the embodiments, the surfactant is polyvinyl pyrrolidone and sodium carboxymethyl cellulose; the concentrations of polyvinyl pyrrolidone and sodium carboxymethyl cellulose in the ultrapure water are both 0.05 g / mL to 0.1 g / mL.

[0043] In some of the embodiments, the concentrations of polyvinyl pyrrolidone and sodium carboxymethyl cellulose in the ultrapure water are both 0.06 g / mL to 0.08 g / mL.

[0044] In some of the embodiments, the concentrations of polyvinyl pyrrolidone and sodium carboxymethyl cellulose in the ultrapure water are both 0.07 g / mL to 0.08 g / mL.

[0045] In other embodiments of the present invention, an alloy material is disclosed, which is prepared from the following raw materials in parts by weight:

[0046]

[0047] In some embodiments, the alloy material is prepared from the following raw materials in parts by weight:

[0048]

[0049] In some embodiments, the alloy material is prepared from the following raw materials in parts by weight:

[0050]

[0051] In some embodiments, the density of the PC (polycarbonate) resin is 1.19 g / cm 3 ~1.21g / cm 3 Its melt index at 300°C and 1.2kg is 8g / 10min±0.3g / 10min.

[0052] In some embodiments, the density of the PMMA (polymethyl methacrylate) resin is 1.18 g / cm 3 ~1.19g / cm 3 Its melt index at 230°C and 3.8kg is 3.5g / 10min±0.3g / 10min.

[0053] In some embodiments, the compatibilizer is SMA-700, the content of maleic anhydride thereof is 16% to 20%, and the melt index at 190° C. and 2.16 kg is 5 g / 10 min±0.5 g / 10 min.

[0054] In some embodiments, the antioxidant is BASF antioxidant.

[0055] In some embodiments, the BASF antioxidant is Irganox 245 or Irganox1076.

[0056] In other embodiments of the present invention, a method for preparing the above alloy material is disclosed, comprising the following steps: mixing PMMA resin and modified polyimide microspheres and stirring them uniformly, then adding PC resin, compatibilizer, and antioxidant and continuing to mix and stir, and then melting, extruding, and granulating in a twin-screw extruder to obtain the alloy material.

[0057] In other embodiments of the present invention, the use of the above alloy material in preparing a tip glass slide of a micro electronic endoscope is disclosed.

[0058] In other embodiments of the present invention, a micro electronic endoscope tip glass slide is disclosed, which is made by injection molding the above alloy material into a cylindrical rod and then cutting it into slices; the thickness of the tip glass slide is 60μm to 220μm.

[0059] In some embodiments, the thickness of the tip glass slide is 60 μm to 180 μm.

[0060] In some embodiments, the thickness of the tip glass slide is 100 μm to 180 μm.

[0061] In the following examples and comparative examples, PC resin is selected from Teijin L-1250Z100, density 1.20g / cm 3 The melt index is 8g / 10min (230℃, 3.8kg). PMMA resin is from Trinseo of the United States Diffuse TM 101, density is 1.19 g / cm 3 The melt index is 3.5 g / 10 min (230°C, 3.8 kg). The compatibilizer is SMA-700, the content of maleic anhydride is 18%, and the melt index is 5 g / 10 min at 190°C and 2.16 kg. The antioxidant is BASF antioxidant Irganox 1076. Other raw materials not specified can be directly obtained from the market.

[0062] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0063] Example 1 Alloy material for preparing the tip glass slide of micro electronic endoscope

[0064] The alloy material for preparing the tip glass slide of a micro electronic endoscope provided in this embodiment is prepared by the following raw materials in parts by weight and steps:

[0065] 1. Preparation of modified polyimide microspheres

[0066] (1) Span-85 and Tween-80 were added to liquid paraffin (LP, continuous phase solvent) at a mass ratio of Span-85:Tween-80=4:1 to prepare a continuous phase solvent with a Span-85 concentration of 10 wt%; 2,2-bis[4-(4-aminophenoxy)phenyl]-hexafluoropropane (diamine monomer) was dissolved in N,N-dimethylformamide (DMF) to prepare a dispersed phase solvent with a concentration of 5 wt%; the continuous phase solvent and the dispersed phase solvent were mixed at a volume ratio of 4:1, and stirred at 60°C for 2 h under nitrogen protection to fully emulsify; then 4,4'-(hexafluoroisopropylene) diphthalic anhydride (dianhydride monomer) powder was added in an equal molar ratio to the diamine monomer, and the polymerization reaction was stirred at 100 rpm for 6 h; N,N-dimethylformamide (DMF) was gradually added dropwise to dilute the system to 1 wt%, thereby obtaining a polyamic acid (PAA) solution;

[0067] (2) adding 0.75% volume of γ-aminopropyltriethoxysilane (KH550) to the polyamic acid (PAA) solution, reacting in situ at 180°C for 1.0h to obtain a polyamic acid (PAA) solution grafted with a silane coupling agent; slowly dripping an excess of a pyridine / acetic anhydride (molar ratio of 1:1) mixture at room temperature to carry out chemical imidization for 4h, collecting the product by centrifugation; then heating at 300°C for 1h to achieve complete imidization, cooling, and obtaining polyimide microspheres grafted with KH550;

[0068] (3) Under nitrogen protection, 1 g of polyimide microspheres grafted with KH550, 1 ml of ultrapure water dispersed with 75 mg of polyvinyl pyrrolidone and 75 mg of sodium carboxymethyl cellulose, and 4 ml of methanol were taken and heated to 70°C. Then, cyclopentadienyl platinum chloride (catalyst, the amount used is 0.05% of phenyl methacrylate) and 1.62 g of phenyl methacrylate were added in sequence. The mixture was reacted at 70°C for 20 h to promote the in-situ polymerization of phenyl methacrylate on the surface of the polyimide microspheres grafted with KH550. After the reaction, the mixture was cooled and fractionated to obtain a modified polyimide microsphere emulsion. After demulsification and drying, the modified polyimide microspheres (modified PI microspheres) were obtained.

[0069] The modified polyimide microspheres prepared in this embodiment have a core-shell structure, with a shell thickness of 10nm to 40nm and a particle size of 100nm to 350nm ( Figure 1 and Figure 2 ), the grafting rate of phenyl methacrylate was measured by weighing method and was 18-23%.

[0070] 2. Preparation of alloy materials

[0071] Take 40 parts of PMMA resin and 1.5 parts of modified polyimide microspheres and mix them evenly, then add 55 parts of PC resin, 5 parts of compatibilizer SMA-700 and 0.2 parts of antioxidant and continue mixing and stirring, and melt, extrude and granulate in a twin-screw extruder to obtain the product.

[0072] The main screw diameter of the twin-screw extruder granulation is 58 mm, the aspect ratio is 60, the heating temperature of the twin-screw extruder is: zone 1 temperature: 220°C, zone 2 temperature: 230°C, zone 3 temperature: 242°C, zone 4 temperature: 242°C, zone 5 temperature: 250°C, zone 6 temperature: 255°C, zone 7 temperature: 242°C, zone 8 temperature: 220°C, zone 9 temperature: 215°C, head temperature: 195°C; the screw extruder speed is 200rpm, the feeding speed is 20r / min, and the pressure is 2MPa.

[0073] Example 2 Alloy material for preparing the tip glass slide of micro electronic endoscope

[0074] This embodiment provides an alloy material for preparing a tip glass slide of a micro electronic endoscope, which is prepared from the following raw materials in parts by weight:

[0075]

[0076] The preparation method is the same as that of Example 1.

[0077] Example 3 Alloy material for preparing the tip glass slide of micro electronic endoscope

[0078] This embodiment provides an alloy material for preparing a tip glass slide of a micro electronic endoscope, which is prepared from the following raw materials in parts by weight:

[0079]

[0080] The preparation method is the same as that of Example 1.

[0081] Example 4 Alloy material for preparing the tip glass slide of micro electronic endoscope

[0082] This embodiment provides an alloy material for preparing a tip glass slide of a micro electronic endoscope, which is prepared from the following raw materials in parts by weight:

[0083]

[0084] The preparation method is the same as that of Example 1.

[0085] Example 5 Alloy material for preparing the tip glass slide of micro electronic endoscope

[0086] This embodiment provides an alloy material for preparing a tip glass slide of a micro electronic endoscope, which is prepared from the following raw materials in parts by weight:

[0087]

[0088] The preparation method is the same as that of Example 1.

[0089] Comparative Example 1

[0090] This comparative example provides an alloy material, which is prepared from the following raw materials in parts by weight:

[0091]

[0092] The preparation method thereof is referred to Example 1.

[0093] Comparative Example 2

[0094] This comparative example provides an alloy material, which is prepared from the following raw materials in parts by weight:

[0095]

[0096] The preparation method comprises the following steps:

[0097] 1. Preparation of polyimide microspheres (PI microspheres)

[0098] (1) Prepare a polyamic acid solution, as in Example 1.

[0099] (2) slowly dripping an excess of a mixture of pyridine / acetic anhydride (molar ratio of 1:1) to carry out chemical imidization for 4 hours, collecting the product by centrifugation, and then heating it at 300°C for 1 hour to achieve complete imidization, and cooling it to obtain polyimide microspheres.

[0100] 2. Preparation of alloy materials

[0101] Refer to Example 1.

[0102] Comparative Example 3

[0103] This comparative example provides an alloy material, which is prepared from the following raw materials in parts by weight, and the preparation method is the same as that of Example 1:

[0104]

[0105] The modified polyimide microspheres are polyimide microspheres grafted with KH550 (PI-g-KH550 microspheres), and the preparation method is the same as steps (1) and (2) of Example 1.

[0106] Comparative Example 4

[0107] This comparative example provides an alloy material, which is prepared from the following raw materials in parts by weight:

[0108]

[0109]

[0110] The preparation method is the same as that of Example 1.

[0111] The preparation formulas of the alloy materials of Examples 1 to 5 and Comparative Examples 1 to 4 are shown in Table 1.

[0112] Table 1

[0113]

[0114] The alloy materials of Examples 1 to 5 and Comparative Examples 1 to 4 were injection molded into cylindrical rods with a thickness of 1700 μm to 2000 μm, ground and polished, and then machined into circular sheets with a thickness of 140 μm, which were then optically cold worked to obtain the tip glass slide of the microelectronic endoscope.

[0115] The following performance tests were performed on the tip glass slides of each micro-electronic endoscope (the Mitsubishi EP-5000, a common material for commercially available endoscope tip glass slides, with a density of 1.02, was processed into a sheet with the same specifications as in Example 2 for performance comparison):

[0116] 1. Anti-puncture performance

[0117] (1) Breakdown voltage

[0118] With reference to the test method of GB / T 1408.1-2016, the test was carried out at a temperature of 25℃±2℃ and a humidity of 60±3%. During the test, the sample (i.e., the endoscope tip protection device) was first pressed with a special electrode, and then tested with a withstand voltage tester according to the designed pressure curve. The DC breakdown voltage was then tested using a rapid voltage-boosting method, with the starting voltage set to 5kv and the voltage-boosting speed set to 0.5kV / s.

[0119] (2) AC voltage resistance

[0120] Refer to the breakdown voltage test. If the product can maintain the specified withstand voltage for 1 minute without breakdown, it is qualified. Use 50Hz AC test, with the initial test voltage at 5kv and increase by 0.5kV until breakdown. Record the maximum voltage value that can be tolerated before breakdown.

[0121] 2. Transparency

[0122] The haze was measured with reference to ASTM D1003-2013 Transparent Plastic Transmittance and Haze, and the minimum value was obtained by testing under a standard C light source of 380nm to 780nm as the transmittance.

[0123] The results are shown in Table 2.

[0124] Table 2

[0125]

[0126] From the results in Table 2, it can be seen that compared with Mitsubishi EP-5000, a common material for commercial endoscope tip glass, the endoscope tip glass made of the alloy materials of Examples 1 to 5 of the present invention has similar transparency, does not weaken the imaging effect of the electronic endoscope, but significantly improves the breakdown performance. Among them, the endoscope tip glass made of the alloy material of Example 2 has high transparency, excellent anti-breakthrough performance, and the best comprehensive effect.

[0127] Compared with the alloy material without polyimide microspheres (Comparative Example 1), the breakdown voltage of the alloy material with unmodified polyimide microspheres (Comparative Example 2) is improved, but due to the poor dispersibility of the unmodified polyimide microspheres, the uniformity of the alloy material is reduced, and its transparency is greatly reduced. Adding polyimide microspheres grafted with KH550 to the alloy material can help the dispersion of the polyimide microspheres to a certain extent, which is helpful for improving the breakdown voltage, but there is still a large gap compared with the modified polyimide microspheres, and the sacrifice of its optical properties is also more obvious (Comparative Example 3). The alloy material of Comparative Example 4 uses the same amount of modified polyimide microspheres as in Example 2, but adjusts the content of PC resin and PMMA resin. Compared with Example 2, its haze is higher, the light transmittance decreases, and the anti-puncture performance is also significantly reduced, and the overall performance is not good.

[0128] The alloy material of Example 2 was injection molded into a cylindrical rod with a thickness of 1700 μm to 2000 μm, and after grinding and polishing, it was cut into circular sheets with thicknesses of 60 μm, 100 μm, 140 μm, 180 μm and 220 μm by mechanical processing, and then optical cold processing was performed to obtain endoscope tip glass slides of different thicknesses. The endoscope tip glass slides were tested for anti-penetration performance and transparency, and the results are shown in Table 3.

[0129] Table 3

[0130]

[0131] From the results in Table 3, it can be seen that when the thickness of the endoscope tip glass is 60μm~220μm, it can meet the requirements of transparency and anti-static breakdown. When the thickness is 100μm~180μm, the transmittance can be greater than 90%, and the breakdown voltage reaches Level 4 required by GB / T17626.2-2018, and the overall effect is better.

[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0133] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A modified polyimide microsphere, characterized in that: The polyimide microspheres grafted with silane coupling agents are reacted with acrylate monomers in a mass ratio of 1:1-2. The polyimide microspheres grafted with silane coupling agents are reacted with polyamic acid solution and silane coupling agent. The concentration of the polyamic acid solution is 0.5wt%-1.5wt%, and the amount of the silane coupling agent added is 0.5%-1% of the volume of the polyamic acid solution.

2. The modified polyimide microsphere according to claim 1, characterized in that: The mass ratio of the polyimide microspheres of the grafted silane coupling agent to the acrylate monomer is 1:1.5-1.7, preferably 1:1.6-1.7; And / or, the concentration of the polyamic acid solution is 0.8wt% to 1.2wt%, and the amount of the silane coupling agent added is 0.7% to 0.8% of the volume of the polyamic acid solution; preferably, the concentration of the polyamic acid solution is 0.9wt% to 1.1wt%, and the amount of the silane coupling agent added is 0.74% to 0.76% of the volume of the polyamic acid solution.

3. The modified polyimide microsphere according to claim 1 or 2, characterized in that: The silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, and γ-aminopropylmethyldimethoxysilane, preferably γ-aminopropyltriethoxysilane. And / or, the acrylate monomer is one or more of benzyl methacrylate, phenyl methacrylate, and naphthyl methacrylate, preferably phenyl methacrylate.

4. A method for preparing modified polyimide microspheres according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) adding the silane coupling agent to the polyamic acid solution, reacting at 170° C. to 190° C. for 0.8 h to 1.2 h, then dropping an excess amount of a mixed solution of pyridine and acetic anhydride in a molar ratio of 0.8 to 1.2:1, reacting at 170° C. to 190° C. for 3 h to 5 h; then heating at 280° C. to 320° C. for 0.8 h to 1.2 h, and cooling to obtain polyimide microspheres grafted with the silane coupling agent; (2) Under the protection of inert gas, the polyimide microspheres grafted with silane coupling agent, ultrapure water dispersed with surfactant, and methanol are heated to 60° C. to 80° C., and then the catalyst and the acrylate monomer are added in sequence, reacted at 60° C. to 80° C. for 18 h to 22 h, and demulsified to obtain modified polyimide microspheres.

5. The method for preparing modified polyimide microspheres according to claim 4, characterized in that: The catalyst is one or more of chloroauric acid tetrahydrate, chloroplatinic acid hexahydrate, ferrous chloride tetrahydrate, cyclopentadiene platinum chloride, and cyclooctadiene platinum chloride, preferably cyclopentadiene platinum chloride; And / or, the amount of the catalyst is 0.03% to 0.1% by mass of the acrylate monomer, preferably 0.05% to 0.1%; And / or, the surfactant is polyvinyl pyrrolidone and sodium carboxymethyl cellulose; the concentrations of polyvinyl pyrrolidone and sodium carboxymethyl cellulose in the ultrapure water are both 0.05 g / mL to 0.1 g / mL, preferably 0.06 g / mL to 0.08 g / mL, and more preferably 0.07 g / mL to 0.08 g / mL.

6. An alloy material, characterized in that: It is prepared from the following raw materials in parts by weight:

7. The alloy material according to claim 6, characterized in that: It is prepared from the following raw materials in parts by weight: Preferably, it is prepared from the following raw materials in parts by weight:

8. The alloy material according to claim 6 or 7, characterized in that: The density of the PC resin is 1.19 g / cm 3 ~1.21g / cm 3 , its melt index at 300°C and 1.2kg is 8g / 10min±0.3g / 10min; And / or, the density of the PMMA resin is 1.18 g / cm 3 ~1.19g / cm 3 , its melt index at 230°C and 3.8kg is 3.5g / 10min±0.3g / 10min; And / or, the compatibilizer is SMA-700, the content of maleic anhydride thereof is 16% to 20%, and the melt index under the conditions of 190° C. and 2.16 kg is 5 g / 10 min±0.5 g / 10 min. And / or, the antioxidant is a BASF antioxidant.

9. A method for preparing the alloy material according to any one of claims 6 to 8, characterized in that: The following steps are involved: The PMMA resin and the modified polyimide microspheres are uniformly stirred, and then the PC resin, compatibilizer and antioxidant are added and stirred continuously, and then melted, extruded and granulated in a twin-screw extruder in sequence to obtain the product.

10. A micro electronic endoscope tip glass slide, characterized in that: The alloy material is obtained by injection molding the alloy material according to any one of claims 6 to 8 into a cylindrical rod and then cutting it into sheets.

Citation Information

Cited By

  • High-performance aramid fiber and preparation method thereof

    CN121228386A